Narratives and dilemmas of local bureaucratic elites: whitehall at the coal face? - Gains, Francesea (2009)
The worlds of local bureaucrats are under researched and under theorized compared with those of civil servants in core executives. Yet local bureaucratic elites, sitting as they do between central states and localities, are key actors in governance network. In England, the role and responsibilities of local bureaucratic elities has been transformed since the days of professionalizsed officers heading departmental structures reporting to committees, firstly by NPM and politicization in the 1980s and 1990s and, more recently, by political management reform introducing a separation of powers. Drawing on interviews in 15 local authorities, this paper examines the changing narratives and dilemmas of local government elites. In particular it explores, but argues against, early expectations that the creation of an elected executive, with considerable devolution of decision-making responsibilities to invididual cabinet member councillors, has meant a move closer to the logics of the `Whitehall mandarin' tradition by local government chief officers. - Reproduced.
Keywords: Civil services